2022
DOI: 10.3389/fnut.2022.844917
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Depressive Symptoms, Dietary Inflammatory Potential, and Sarcopenia: Mediation Analyses

Abstract: BackgroundSarcopenia is a major public health problem. Depressive symptoms and dietary inflammatory potential play important roles in the development of sarcopenia. We aimed to disentangle the relationships between depressive symptoms, dietary inflammatory potential, and sarcopenia.MethodsA total of 6,082 participants from the National Health and Nutrition Examination Survey (NHANES) were included in the analyses. Sarcopenia was defined according to the Foundation for the National Institutes for Health (FNIH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…Secondly, depression data and LPA assessment in our study were based on self–reported questionnaire. However, PHQ9 and PAQ were regarded as “gold standard” criteria for large population–based studies, which has been applied in several previous publications ( 75 , 76 ). In addition, DII score calculated by 24–h dietary recall may not only cause imprecise estimates due to inability in measuring day–to–day variability in dietary intake, but also characterize population or group intake rather than a measure of individual intake ( 77 ).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, depression data and LPA assessment in our study were based on self–reported questionnaire. However, PHQ9 and PAQ were regarded as “gold standard” criteria for large population–based studies, which has been applied in several previous publications ( 75 , 76 ). In addition, DII score calculated by 24–h dietary recall may not only cause imprecise estimates due to inability in measuring day–to–day variability in dietary intake, but also characterize population or group intake rather than a measure of individual intake ( 77 ).…”
Section: Discussionmentioning
confidence: 99%
“…For dose-response meta-analysis, we included seven studies that divided DII into at least three categories, and two studies were excluded ( 23 , 44 ). Setting the reference DII level as −2.68, we found a significant non-linear dose-response relationship between DII and sarcopenia ( P = 0.012 for non-linearity).…”
Section: Resultsmentioning
confidence: 99%
“…This provides us with a macro dietary direction to prevent and control sarcopenia, which reduces the total incidence of sarcopenia in the population by increasing the intake of anti-inflammatory diets. At the same time, a mediation analysis [ 26 ] showed that the DII and depressive symptoms are related to sarcopenia. Symptoms of depression play a significant mediating role on the related manifestations of the DII and sarcopenia (muscle strength, muscle mass, and physical performance).…”
Section: Discussionmentioning
confidence: 99%
“… Forest plot of the risk of sarcopenia in subjects with a high DII vs. a low DII [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. …”
Section: Figurementioning
confidence: 99%